FORMULASI SEDIAAN SERUM DARI KULIT BUAH DURIAN BERBAGAI VARIETAS (Durio zibethinus Murray) LOKAL, MONTONG DAN MUSANG KING - Hari Untarto Swandono; Sony Andika Saputra; Maria Magdalena Riyaniarti Estri Wuryandari; M. Nur Husna (MEDIA ILMU KESEHATAN, 2026)
Background: Durian peel (Durio zibethinus Murr.), which is often discarded as agricultural waste, contains bioactive compounds such as flavonoids and tannins that exhibit antibacterial properties, particularly against acne-causing bacteria Objective: This study aimed to evaluate the physical characteristics and stability of a serum formulation prepared with durian peel extract (Durio zibethinus Murr.) at a concentration of 15% and to compare the physical stability among different durian varieties.Methods: The durian peel extract was obtained using the maceration method with 96% ethanol as the solvent and then formulated into a serum preparation. Physical quality evaluations included tests for color, homogeneity, pH, spreadability, adhesion, and viscosity. Results: The Musang King variety produced the best formulation, characterized by a yellowish-brown color and homogeneous appearance. The pH remained stable between 4.67 and 6.65 before and after stability testing. Conclusion: The durian peel extract–based serum demonstrated good physical quality and stable characteristics during storage, suggesting its potential use as a natural active ingredient in cosmetic formulations for acne-prone skin care